Phonological Awareness Intervention Research: A Critical Review of the Experimental Methodology - Troia, Gary A. (Reading research quarterly, 1999)
The methodological rigor of 39 studies of phonological awareness intervention was evaluated based on internal and external validity criteria. The internal validity criteria encompassed general design characteristics, measurement, and statistical treatment, while the external validity criteria included research hypotheses, participant selection and description, and generalization and maintenance measures. The most serious methodological flaws observed in many of the studies were (a) nonrandom assignment of participants to conditions; (b) failure to control for Hawthorne effects by providing alternate interventions to control groups; (c) insufficient or nonexistent assurance of fidelity of treatment; (d) poor measurement sensitivity; and (e) inadequately described samples. Only seven studies met two thirds or more of all the evaluative criteria, although all of these investigations demonstrated at least one fatal flaw. The reported findings are compared with those of two similar methodological reviews. Suggestions for improvement of future intervention research are provided. /// [Spanish] El rigor metodológico de 39 estudios de intervención en conciencia fonológica fue evaluado sobre la base de criterios de validez interna y externa. Los criterios de validez interna comprendieron características generales de diseño, mediciones y tratamiento estadístico, en tanto que los criterios de validez externa incluyeron las hipótesis de la investigación, la selección y descripción de los participantes y la generalización y mantenimiento del efecto fuera de la situación experimental. Las fallas metodológicas más serias observadas en muchos de los estudios fueron (a) no asignar al azar a los participantes a las distintas condiciones; (b) ausencia de control de los efectos Hawthorne, al proveer intervenciones alternativas a los grupos de control; (c) insuficiencia o ausencia de certeza en la exactitud del tratamiento; (d) escasa sensibilidad de las mediciones y (e) muestras descriptas inadecuadamente. Sólo siete estudios reunieron dos tercios o más de todos los criterios de evaluación, aunque todas estas investigaciones demostraron al menos una falla fatal. Los hallazgos reportados se comparan con los de dos revisiones metodológicas similares. Se hacen sugerencias para mejorar las futuras investigaciones de intervención. /// [German] Die methodologische Rigorosität von 39 Studien phonologischer Eingriffe zur Bewußheitsförderung wurde aufgrund intern und extern gültiger Kriterien bewertet. Die intern angewandten Bewertungskriterien schließen generelle Auslegungscharakteristiken, Bemessung und statistische Behandlung bzw. Auswertung ein, während die extern gültigen Kriterien Forschungshypothesen, Teilnehmerauswahl und Beschreibung, sowie Allgemein- und Aufrechterhaltungsmaßnahmen einschließen. Der schwerwiegendste methodologische Tadel an beobachteten Fehlern bei vielen der Studien lag in (a) nicht-wahllose Bestimmung der den Bedingungen unterworfenen Teilnehmer; (b) Versäumen von Kontrollen gemäß den Hawthorne Effekten durch Einfügen alternativer Eingriffe zur Kontrolle der Gruppen; (c) unzureichende oder nicht existierende Zusicherung der genauen Gleichbehandlung der Mittel; (d) geringe Beimessung an Einfühlungsvermögen; und (e) mangelhafte Beschreibung der Muster. Lediglich sieben Studien erfüllten zwei Drittel oder mehr aller Bewertungskriterien, obwohl alle diese Untersuchungen mindesterns einen entscheidenden Fehler aufwiesen. Die berichteten Ergebnisse wurden mit jenen aus zwei methodologisch ähnlichen Rezensionen verglichen. Es wurden Verbesserungsvorschäge für zukünftige vermittelnde Forschung angemerkt. /// [French] On a évalué la rigueur méthodologique de 39 études d'interventions relatives à la conscience phonétique en se basant sur des critères de validité interne et externe. Les critères de validité interne comprennent les caractéristiques générales du plan expérimental, la mesure, le traitement statistique, tandis que les critères de validité externe incluent les hypothèses de recherche, la sélection et la description des participants, les mesures concernant la généralisation et le maintien. Les points faibles les plus sérieux observés dans de nombreuses études ont été: a) répartition non aléatoire des participants dans les conditions expérimentales; b) manque de contrôle de l'effet Hawthorne en faisant alterner les interventions des groupes contrôle; c) fidélité du traitement insuffisante ou inexistante; d) sensibilité de la mesure faible; e) échantillons décrits de manière inadéquate. Seules sept études satisfont à au moins deux tiers de la totalité des critères d'évaluation, mais toutes présentent neanmoins au moins un défaut fatal. Les résultats obtenus sont comparés avec deux études de méthodologie. Le texte présente des suggestions pour améliorer les futures interventions de recherche.